Toxicological evaluation of silver nanoparticles and silver nitrate in rats following 28 days of repeated oral exposure. Issue 2 (21st March 2016) - Qin, Guangqiu; Tang, Song; Li, Shibin; Lu, Haoliang; Wang, Yanwu; Zhao, Peng; Li, Bin; Zhang, Jiehong; Peng, Liang
ABSTRACT: The increasing application of silver nanoparticles (AgNPs) has been raising concerns about their potential adverse effects to human and the environment. However, the knowledge on the systemic toxicity of AgNPs in mammalian systems is still limited. The present study investigated the toxicity of PVP‐coated AgNPs in rats treated with repeated oral administration, and compared that with equivalent dose of AgNO3 . Specifically, one hundred male and female rats were orally administrated with particulate or ionic forms of silver (Ag) separately at doses of 0.5 and 1 mg kg −1 body weight daily for 28 days. The results reveal no significant toxic effects of AgNPs and AgNO3 up to 1 mg kg −1 body weight, with respect to the body weight, organ weight, food intake, and histopathological examination. Ag distribution pattern in organs of rats treated with AgNPs was similar to that of AgNO3 treated rats, showing liver and kidneys are the main target organs followed by testis and spleen. The total Ag contents in organs were significantly lower in the AgNPs treated rats than those in the AgNO3 treated rats. However, the comparisons between AgNPs and AgNO3 treatments further indicated more potent of AgNPs in biochemical and hematological parameters in rats, including red blood cell count (RBC), platelet count (PLT), white blood cell count (WBC) and aspartate transaminase (AST). Results of this study suggested that particulate Ag at least partially contributed to the observed toxicity of AgNPs, and both ionic and particulate Ag should be taken into consideration in toxicological evaluation of AgNPs. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 609–618, 2017.